2021
DOI: 10.15294/jere.v10i1.50048
|View full text |Cite
|
Sign up to set email alerts
|

Development Of Android-Based Interactive Jobsheet On Electrical Measuring Equipment Materials In Vocational School

Abstract: This study aims to 1) the feasibility of the developed android-based interactive jobsheet, 2) the effectiveness of the developed android-based interactive jobsheet. 3) Student responses to the developed android-based interactive worksheets. This study uses the ADDIE development model. The experimental design in this study used the One-Group Pretest-Postest Design. The research sample was class X students majoring in Light Vehicle Engineering (TKR). Data analysis used normality test, homogeneity test, product f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…This finding is consistent with previous research showing the beneficial effects of tailor-made training aids for the learning process on student aptitude [4]. Even though some research indicated a moderate impact, the aggregate results nonetheless demonstrated the advantages of raising pupils' skill levels [13], [14], [30]. Research in the field of EMC has been done a lot before.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with previous research showing the beneficial effects of tailor-made training aids for the learning process on student aptitude [4]. Even though some research indicated a moderate impact, the aggregate results nonetheless demonstrated the advantages of raising pupils' skill levels [13], [14], [30]. Research in the field of EMC has been done a lot before.…”
Section: Discussionsupporting
confidence: 90%
“…This is because each school has different characteristics and different problems. Increasing the research sample through various vocational schools will increase the accuracy and acceptance of the products developed [13].…”
Section: N V O T E Kmentioning
confidence: 99%
“…The findings are corroborated by earlier studies that were carried out in the same field. According to (Badruttamam & Hadromi, 2021;Richardo et al, 2023), their research used video-based learning, which considerably boosted student learning outcomes because the video content included audio, text, and visuals of the learning material provided. Furthermore, prior research has demonstrated that using a tutorial video in the vocational education process has improved student learning outcomes.…”
Section: Discussionmentioning
confidence: 99%